Tripartite immune cell co‐operation in the Bacillus Calmette Guérin‐induced activation of γδ T cells. Issue 7 (25th June 2013) - Fowler, Daniel W; Copier, John; Dalgleish, Angus G; Bodman‐Smith, Mark D
Abstract : γδ T cells contribute to immunosurveillance of pathogenic infections and malignant transformations; however, mechanisms of activation have yet to be fully defined. In this study we demonstrate a novel mechanism by which human Vδ2 + γδ T cells are activated by the model pathogen Bacillus Calmette Guérin (BCG). We show in vitro that Vδ2 cell cytokine production and cytotoxic activity in response to BCG are dependent on both dendritic cells (DCs) and memory CD4 + αβ T cells (CD4 T cells). We found that Vδ2 cells are indirectly activated by BCG in an interleukin (IL)‐12p70‐dependent manner, and that DC production of the IL‐12p70 responsible for Vδ2 cell activation requires Toll‐like receptor 2/4 ligands from BCG and interferon (IFN)‐γ from memory CD4 T cells. Our data suggest that Vδ2 cell responses to BCG are dependent on the activation of IFN‐γ‐producing memory CD4 T cells, and provide novel insight into the complex interplay between cells of the innate and adaptive immune response.